Antibacterial Activity of Lemongrass (Cymbopogon nardus) Ethanolic Extract - Waras Nurcholis; Mira Takene; Ratna Puspita; Lisnawati Tumanggor; Eka Nurul Qomaliyah; Muhammad Maftuchin Sholeh (Current Biochemistry, 2019)
Infectious diseases are a disease caused by bacteria such as Escherichia coli and Staphylococcus aureus. One way to overcome the disease by using antibiotics. However, wise use can lead to antibiotic resistance, so many bacteria are resistant to antibiotics. Therefore it is necessary to search the natural compounds as antibacterials, one of them by using lemongrass (Cymbopogon nardus). This study aims to determine the effectiveness of leaf extracts, stems, and roots lemongrass as antibacterial. The method used in this research is the disc method. Bacteria used are E. coli and S. aureus. The results show extracts of roots, stems, and leaf has activity against S. aureus, while E. coli shows no activity as antibacterial, it can be possible because of the different properties of the bacteria. Keywords: anti-bacteria, lemongrass, Escherichia coli, Staphylococcus aureus